2015
DOI: 10.7439/ijbr.v6i9.2488
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Post Operative Complications of Open Prostatectomy (Fryer’s) Versus Trans Urethral Resection of Prostate

Abstract: Aims & objectives: To compare post-operative complications between open prostatectomy (FREYER`S) and T.U.R.P. Material and Methods: Patients, who were candidates for prostate surgery & had been referred to urology outpatient clinic in our hospital between December 2011 to September 2013, were enrolled for the study. These patients were then divided in two groups -A and B randomly, by using the process of randomization. Group A comprised of patients for open prostatectomy and Group B of patients for T.U.R.P. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The rate of UTI in the early post-op period was almost similar with other studies in other parts of the world but Sagarkumar Gupta et al reported higher rates of UTI in TURP ( 8 , 9 , 21 , 22 , 25 ).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The rate of UTI in the early post-op period was almost similar with other studies in other parts of the world but Sagarkumar Gupta et al reported higher rates of UTI in TURP ( 8 , 9 , 21 , 22 , 25 ).…”
Section: Discussionsupporting
confidence: 86%
“…Another study from Ethiopia found a 4.6% rate of transfusion after STVP( 7 ). A similar finding is reported by Sagarkumar Gupta et al with no significant difference in rates of transfusion with a rate of 8% and 12% for STVP and TURP respectively ( 22 )…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Postoperative incontinence occurred only in the OP group in this study (13.8%). Other workers have noted postoperative incontinence while performing OP [ 29 , 30 ]. Damage to the external sphincter is the most frequent cause of postoperative incontinence following open prostatectomy.…”
Section: Discussionmentioning
confidence: 99%